Assessment of phosphate-solubilizing microbes isolated from indigenous organic-biofertilizers for enhancing plant growth in acid-stressed - NADIA NURANIYA KAMALUDDIN; IRWANDHI IRWANDHI; PARTIKA ARUM; YUNUS SETIAWAN; FIQRIAH HANUM KHUMAIRAH; NUR PRIHATININGSIH; TUALAR SIMARMATA (Society for Indonesian Biodiversity, 2025)
Abstract. Kamaluddin NN, Irwandhi, Arum P, Setiawan Y, Khumairah FH, Prihatiningsih N, Simarmata T. 2025. Assessment of phosphate-solubilizing microbes isolated from indigenous organic-biofertilizers for enhancing plant growth in acid-stressed. Biodiversitas 26: 1325-1333. Indonesia is one of the countries that produces enormous amounts of organic waste every year, but most of this organic waste has not been appropriately managed, thereby worsening climate change. One alternative solution that is environmentally friendly and sustainable is converting organic waste into Indigenous Organic Biofertilizers (IOB). This process involves the controlled decomposition of organic waste, which is then enriched with beneficial microbes, such as Phosphate Solubilizing Microbes (PSM). PSM from IOB can be a candidate for a biofertilizer inoculant that can withstand environmental stress, especially acidity stress caused by climate change. This research aimed to screen, characterize, and assess the biochemical activity of isolates and molecularly identify PSM from IOB that are resistant to acidity stress. In this research, characterization was carried out in the form of macroscopic and microscopic observations, resistance to acidity stress, phosphate dissolution index, production of Indole-3-Acetic Acid (IAA), compatibility test, and identification of the 16S rRNA gene. Bacterial isolates with codes F1ZN1, F2P, and F6P, while fungal isolates F4A, F5B, and F5C were the best PSM isolates. This isolate can produce IAA with a high category of around 57.28-105.94 ppm (bacteria) and a medium category of around 18.34-24.33 ppm (fungi). Apart from that, these isolates are compatible with the isolates to work synergistically. Through molecular identification of 16S rRNA sequencing, F1ZN1 was identified as Enterobacter cloacae strain Ec030, F2P was identified as E. cloacae strain UT25, and F6P was identified as E. cloacae strain ABRL064. These results highlight the potential of PSM isolates from IOB as an effective biofertilizer inoculant candidate for increasing plant growth in environmental stress (acidity) amidst climate change.